Clarifying value in use and value creation process - Popesku, Mihajlo (2015)
Current marketing literature, regardless of its underlying paradigm/logic, lacks consensus on how to conceptualise value creation, how to define what it entails, along with by whom, how, where and when it is created (Voima et al., 2010). It is no surprise then that the value creation process is often described as a ‘black box’ (Grönroos, 2011b; Leroy et al., 2013). In this doctoral research the customer’s perspective on value creation has been advocated. Research was conducted using mixed methods in the context of digital camera usage. It was found that value creation process consists of inputs (resources, customer and other socio-economic actors), 5 value creation phases (this is actually the content of black box: usage episode initiation, resource selection, resource adjustment, resource integration and evaluation) and outputs (side effects and value-in-use as a mix of instrumental benefits, experiential benefits, symbolic benefits and sacrifices;). Simultaneously to value creation, each consumption episode provides an opportunity for customer’s episodic learning that can result in customer’s augmented or new knowledge, skills and experience. Research found value to be episodic phenomenon, while value creation consistent with Roggeveen et al. (2012), was found to be cyclical and non-linear, showing how unpredictable the unique value creation path of an individual customer can be. This indicates that a value creation episode can evolve in unique ways depending on the sequence of value creation phases, given that customers may revisit already visited value creation phases (unless resources are not destroyed). In this way, while the study acknowledges the idiosyncrasies of individual customers’ approaches, on the other hand, it provides a theoretically structured view of this inherently idiosyncratic process.